RIBA, PERBANKAN SYARIAH, DAN INVESTASI SECARA ISLAMI DI KALANGAN REMAJA - Dinar Marfianti Azzahra; Asyari Hasan; Ghabrield Akhmad Nadzar; Muhammad Ilham Kurniawan; Raditya Andrian Aji Baskoro; Raihan Aqilah Putera Deza; Redita Adriana Irmadela (Universitas Muhammadiyah Prof Dr Hamka, 2021)
The research objective is to look at adolescents'opinion about usury, interest in saving in Islamic banks and investing in Islamic methods. One of the factors affecting economic development in Indonesia is the increase or decrease in interest rates. By using e-view software, the approach used in this study is a qualitative approach using descriptive analysis. The result of this research show that riba is an addition, but this addition creates injustice, this is explained from various sources including Alquran. Islamic financial institutions have a very important role of regulating the Islamic financial system, the principles on this matter are based on the Qur’an and the Sunnah of the Prophet. Keywords: Interest Money; Usury; Investment; Islamic Financial; Islamic Economy; Islamic Institution in Indonesia